Associations of Total, Cognitive/Affective, and Somatic Depressive Symptoms and Antidepressant Use With Cardiovascular Disease–Relevant Biomarkers in HIV: Veterans Aging Cohort Study. Issue 5 (June 2020) - Stewart, Jesse C.; Polanka, Brittanny M.; So-Armah, Kaku A.; White, Jessica R.; Gupta, Samir K.; Kundu, Suman; Chang, Chung-Chou H.; Freiberg, Matthew S.
ABSTRACT: Objective: We sought to determine the associations of total, cognitive/affective, and somatic depressive symptoms and antidepressant use with biomarkers of processes implicated in cardiovascular disease in HIV (HIV-CVD). Methods: We examined data from 1546 HIV-positive and 843 HIV-negative veterans. Depressive symptoms were assessed using the Patient Health Questionnaire-9, and past-year antidepressant use was determined from Veterans Affair pharmacy records. Monocyte (soluble CD14 [sCD14]), inflammatory (interleukin-6 [IL-6]), and coagulation (D-dimer) marker levels were determined from previously banked blood specimens. Linear regression models with multiple imputation were run to estimate the associations between depression-related factors and CVD-relevant biomarkers. Results: Among HIV-positive participants, greater somatic depressive symptoms were associated with higher sCD14 (exp[ b ] = 1.02, 95% confidence interval [CI] = 1.00–1.03) and D-dimer (exp[ b ] = 1.06, 95% CI = 1.00–1.11) after adjustment for demographics and potential confounders. Further adjustment for antidepressant use and HIV factors slightly attenuated these relationships. Associations were also detected for antidepressant use, as selective serotonin reuptake inhibitor use was related to lower sCD14 (exp[ b ] = 0.95, 95% CI = 0.91–1.00) and IL-6 (exp[ b ] = 0.86, 95% CI = 0.76–0.96), and tricyclic antidepressant use was related to higher sCD14 (exp[ b ] = 1.07, 95% CI = 1.03–1.12) and IL-6 (exp[ b ] = 1.14, 95% CI = 1.02–1.28). Among HIV-negative participants, total, cognitive/affective, and somatic depressive symptoms were associated with higher IL-6, and tricyclic antidepressant use was related to higher sCD14. Conclusions: Our novel findings suggest that a) monocyte activation and altered coagulation may represent two pathways through which depression increases HIV-CVD risk and that b) tricyclic antidepressants may elevate and selective serotonin reuptake inhibitors may attenuate HIV-CVD risk by influencing monocyte and inflammatory activation.